Existence of a solution asymptotic to a periodic solution of integro-differential systems with a fixed memory length (Neliniini Kolyvannya, 2025)
We study the existence of solutions asymptotic to periodic solutions for integro-differential equations with a fixed memory length. This paper is dedicated to the memory of Academician Oleksandr Boichuk.